2018
DOI: 10.1159/000494164
|View full text |Cite
|
Sign up to set email alerts
|

CDC27 Facilitates Gastric Cancer Cell Proliferation, Invasion and Metastasis via Twist-Induced Epithelial-Mesenchymal Transition

Abstract: Background/Aims: Lymph node metastasis is the primary cause of cancer-related death among patients with gastric cancer (GC), and cell division cycle 27 (CDC27) promotes the metastasis and epithelial-mesenchymal transition in many cancers. Till now, the mechanisms underlying CDC27-induced the epithelial-mesenchymal transition (EMT) of GC are still unclear. Methods: We analyzed the expression levels of CDC27 and EMT-related biomarkers using immunohistochemistry and Western blot in 60 cases of GC tissues, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 18 publications
(20 reference statements)
0
19
0
Order By: Relevance
“…As a core subunit of APC/C, CDC27 can bind CDH1 or CDC20, playing a key role in the process of recognizing and degrading target substrates. In recent years, several studies have reported that CDC27 can facilitate cell proliferation, migration and invasion in some types of cancers (23)(24)(25). Nevertheless, few studies indicated the opposite influence of CDC27 on cell functions and patients' survival analysis (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…As a core subunit of APC/C, CDC27 can bind CDH1 or CDC20, playing a key role in the process of recognizing and degrading target substrates. In recent years, several studies have reported that CDC27 can facilitate cell proliferation, migration and invasion in some types of cancers (23)(24)(25). Nevertheless, few studies indicated the opposite influence of CDC27 on cell functions and patients' survival analysis (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that overexpression of CDC27 promotes the proliferation of colorectal cancer and the cell-dependent approach promotes the ability to transfer and form balls (Qiu et al, 2017). Additionally, Xin et al (2018) demonstrated that the CDC27 expression was obviously increased in gastric cancer tissues, and significantly correlates with EMT-related biomarkers and poor 5year overall survival. We speculate that CDC27 participates in the development of NSCLC by regulating the cell cycle, apoptosis, and inflammation levels.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that dysregulation of APC/C contribute to tumorigenesis in cancers. 24 Emerging evidence has revealed the role of CDC27 in the invasion and metastasis in several tumors, including colorectal, 25 gastric, 26 and pancreatic 27 cancer. The CDC27 protein contains two major functional regions, the Apc3 region and the TPR region.…”
Section: Discussionmentioning
confidence: 99%